Pewne Rozwiązanie dla Anizotropowej Płyty Prostokątnej o Zmiennej Sztywności - Solecki, R. (Engineering Transactions, 1963)
Making use of the equations derived in [1], the problem of simply supported, clamped or free plates is analysed, The numerical example concerns the bending problem of an isotropic square: plate clamped along the contour and having linearly variable rigidity.